Understanding the Psychological and Financial Correlates for Consumer Credit Use; - Ertuğrul, Seyit; Sayar, Alperen; Şahin, Türkay; Çakar,Tuna; Ertuğru, Seyit (Sosyoekonomi Society, 2024)
This study investigated the behavioural and cognitive predictors of consumer credit usage to develop a behavioural credit risk assessment procedure for a factoring company. Participants completed surveys measuring personality traits, self-esteem, material and monetary values, compulsive and impulsive buying tendencies, self-control, and impulsiveness. Financial surveys also assessed financial literacy and knowledge of financial concepts. The results indicated that extraversion, conscientiousness, emotional stability, and experiential self-control were significant predictors of consumer credit usage. These findings suggest that a finance company can use these personality traits and financial characteristics to develop a more accurate and effective credit risk assessment procedure, such as psychometric tests. © 2024, Sosyoekonomi Society. All rights reserved.
Tüketici Kredisi Kullanımının Altında Yatan Psikolojik ve Finansal Değişkenleri Anlamak
Keywords: Consumer behaviour; Behavioural economics; Financial literacy; Factoring; Consumer credit; İşletme; İşletme Finans